2017
DOI: 10.3847/1538-3881/aa86ac
|View full text |Cite
|
Sign up to set email alerts
|

Light and Heavy Element Abundance Variations in the Outer Halo Globular Cluster NGC 6229

Abstract: NGC 6229 is a relatively massive outer halo globular cluster that is primarily known for exhibiting a peculiar bimodal horizontal branch morphology. Given the paucity of spectroscopic data on this cluster, we present a detailed chemical composition analysis of 11 red giant branch members based on high resolution (R ≈ 38,000), high S/N (> 100) spectra obtained with the MMT-Hectochelle instrument. We find the cluster to have a mean heliocentric radial velocity of -138.1

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 117 publications
(197 reference statements)
0
14
0
Order By: Relevance
“…These results were later confirmed by Yong et al (2016), who analysed a large sample of CaT spectroscopy of this cluster and found a range of [Fe/H] values spanning ∼ 1 dex ( = 0.17). This was followed up by Johnson et al (2017) who used a large sample of high and medium resolution spectra of NGC 6273 members, and found a dispersion in [Fe/H] of ∼ 0.2 dex, with a full range of values from [Fe/H] ∼ −2 to −1 dex 1 . Additionally, they find some evidence for three discrete sub-populations in metallicity space with each sub-populations exhibiting the classic signatures of MPs.…”
Section: Ngc 6273 (M19)mentioning
confidence: 96%
See 1 more Smart Citation
“…These results were later confirmed by Yong et al (2016), who analysed a large sample of CaT spectroscopy of this cluster and found a range of [Fe/H] values spanning ∼ 1 dex ( = 0.17). This was followed up by Johnson et al (2017) who used a large sample of high and medium resolution spectra of NGC 6273 members, and found a dispersion in [Fe/H] of ∼ 0.2 dex, with a full range of values from [Fe/H] ∼ −2 to −1 dex 1 . Additionally, they find some evidence for three discrete sub-populations in metallicity space with each sub-populations exhibiting the classic signatures of MPs.…”
Section: Ngc 6273 (M19)mentioning
confidence: 96%
“…They also identified a population of at least five peculiar "low-" stars that have [ /Fe] ∼ 0.0 and low [Na/Fe] and [Al/Fe] abundances. 1 We note that while Johnson et al (2015Johnson et al ( , 2017 used the 'spectroscopic' approach to determine the Fe spread within M 19, which can lead to an artificial broadening of the intrinsic Fe spread (e.g., Lardo et al 2016;Mucciarelli et al 2016), the large spread found in M 19 (∼ 1 dex) argues that a large and true Fe spread exists within this cluster. Future work using the "photometric" method on this cluster will be able to confirm this.…”
Section: Ngc 6273 (M19)mentioning
confidence: 98%
“…In particular, clusters possessing warmer blue HB populations and larger present-day masses tend to exhibit more extreme [O/Na] and [Mg/Al] abundance ranges (Carretta et al 2007(Carretta et al , 2010a; Gratton et al 2010). A significant fraction of clusters with M V < ∼ −8 exhibit variations in Fe-peak and s-process abundances as well, and some evidence indicates that many of these "Fe-complex" or "Type II" clusters may be the remnant cores of former dwarf galaxies (e.g., Da Costa 2016;Johnson et al 2017a;Marino et al 2018). In fact, Lee et al (2007) suggests that most or all clusters with significant blue HB populations have an accretion origin.…”
Section: Introductionmentioning
confidence: 99%
“…Clusters such as M 4(Marino et al 2008;Villanova & Geisler 2011) also exhibit significant composition gaps but do not contain E stars Lapenna et al (2015),. andJohnson et al (2017aJohnson et al ( , 2018). The literature sources were shifted to have approximately the same upper [O/Fe] and lower [Na/Fe] bounds as NGC 6402, and were resampled 10 4 times.…”
mentioning
confidence: 99%
“…For NGC 6569, which has E(B − V )>0.55 (see Section 4.1), a near-infrared calibration is preferred over those using V-band magnitudes (e.g., Starkenburg et al 2010;Saviane et al 2012;Carrera et al 2013) Given the moderately high resolution and S/N of our data, the internal abundance uncertainties are dominated by errors in model atmosphere parameter determinations. For T eff , we have adopted an uncertainty value of 100 K based on the log ò(Fe I) versus lower excitation potential plots, previous comparisons of spectroscopic and photometric temperatures using low reddening clusters (e.g., Johnson et al 2015aJohnson et al , 2017c, and the scatter present in a plot of J-K S versus spectroscopic temperature for the current data set. Similarly, we have adopted a conservative log(g) uncertainty of 0.15 cgs for all stars based on an examination of the scatter present when binning the data into groups spanning ∼100 K each (see also Section 4.1 and Figure 4).…”
Section: Calcium Triplet [Fe/h] Determinationsmentioning
confidence: 99%